Functional assessment of muscle response in lower limbs of tumbling gymnasts through tensiomyography - Nicolás Rojas-Barrionuevo (Revista de la Facultad de Medicina, 2016)
Introduction: Jumping capacity, a distinctive technical skill of tumbling gymnasts, is associated to a successful performance in training and competition; hence the need for an individualized, precise and localized assessment of the most demanded muscle structures. Objective: To assess muscle response of the flexo-extension structure in the knee joint and the extension of the ankle joint in a sample of 12 high-performance male gymnasts. Materials and methods: An acrobatic training protocol including sets of forward somersault in tumbling track was conducted. The contraction time, delay time and deformation of muscle belly were evaluated, and the muscular response speed was calculated using tensiomyography before and after the training intervention in different periods of time. Results: Significant differences were found (p<0.05) according to the muscle group involved, where rectus femoris and biceps femoris presented greater enhancement and shortening of the contraction and delay time. Major differences appeared between agonist-antagonist muscles (vastus lateralis-biceps femoris) (p<0.05) due to a decrease in the contraction and delay speed in vastus medialis (p<0.001). Conclusions: Tensiomyography allows estimating the states of activation-enhancing of the musculature responsible of jumping in tumblers, as well as planning the training based on the state of muscle fatigue.